Attitudes and barriers associated with seasonal influenza vaccination uptake among public health students; a cross-sectional study - Christopher J. Rogers; Kaitlin O. Bahr; Stephanie M. Benjamin (BMC, 2018)
Abstract Background Although research has explored influenza vaccination uptake among medical and college students, there is a dearth of research in understanding influenza vaccination uptake and attitudes toward the vaccine among future public health practitioners. Undergraduate public health students represent future public health practitioners who may be a significant educational resource for health information, including the importance of vaccinations. Methods This cross-sectional study utilized survey data from 158 undergraduate public health students attending a large public university in Southern California. The survey assessed public health students' attitudes and beliefs towards the seasonal influenza vaccine and seasonal vaccination rates among this population. Results Over 88% of respondents reported having been encouraged to receive the seasonal influenza vaccine, while only 43.0% reported receipt. Of the students who reported not receiving the vaccine, 49.4% believed it may give them the flu, 30.4% believed there may be dangerous side effects, and 28.9% believed they were not at risk for contracting the flu. Access to health care practitioners (OR: 3.947, 95% CI [1.308-11.906]) and social encouragement (OR: 3.139, 95% CI [1.447-6.811]) were significantly associated with receipt of the seasonal influenza vaccine. Conclusion As public health program curriculum includes information about seasonal influenza vaccination and 68% of the sample were seniors soon to be exiting the program with an undergraduate degree in public health education, this low seasonal influenza vaccination rate is disturbing. This study may add to the body of data demonstrating how knowledge of the vaccine does not always guarantee vaccine uptake. Results of the current study suggest that it may be beneficial to provide additional information targeted to public health students, aimed at mediating safety concerns and increasing social pressure to assist in improving vaccine acceptance and rates in this population. Maximizing seasonal influenza vaccination uptake by addressing attitudes, barriers and misperceptions may not only improve vaccination rates among public health students, but also in communities served by these future public health practitioners.